Structure, expression, and chromosomal localization of the type I human vasoactive intestinal peptide receptor gene. - Sreedharan, S P (1995)
Vasoactive intestinal peptide (VIP) and other members of the pituitary adenylyl cyclase-activating peptide (PACAP) and secretin neuroendocrine peptide family are recognized with specificity by related G protein-coupled receptors. We report here the cloning, characterization, and chromosomal location of the gene encoding the human type I VIP receptor (HVR1), also termed the type II PACAP receptor. The gene spans approximately 22 kb and is composed of 13 exons ranging from 42 to 1400 bp and 12 introns ranging from 0.3 to 6.1 kb. Primer extension analysis with poly(A)+ RNA from human HT29 colonic adenocarcinoma cells indicated that the transcription initiation site is located at position -110 upstream of the first nucleotide (+1) of the translation start codon, and 75 nt downstream of a consensus CCAAT-box motif. The G+C-rich 5' flanking region contains potential binding sites for several nuclear factors, including Sp1, AP2, ATF, interferon regulatory factor 1, NF-IL6, acute-phase response factor, and NF-kappa B. The HVR1 gene is expressed selectively in human tissues with a relative prevalence of lung > prostate > peripheral blood leukocytes, liver, brain, small intestine > colon, heart, spleen > placenta, kidney, thymus, testis. Fluorescence in situ hybridization localized the HVR1 gene to the short arm of human chromosome 3 (3p22), in a region associated with small-cell lung cancer.